EURADOS education and training activities. (24th September 2019) - Alves, J G; Fantuzzi, E; Rühm, W; Gilvin, P; Vargas, A; Tanner, R; Rabus, H; Lopez, M A; Breustedt, B; Harrison, R; Stolarczyk, L; Fattibene, P; et al.
Abstract: This paper provides a summary of the Education and Training (E&T) activities that have been developed and organised by the European Radiation Dosimetry Group (EURADOS) in recent years and in the case of Training Courses over the last decade. These E&T actions include short duration Training Courses on well-established topics organised within the activity of EURADOS Working Groups (WGs), or one-day events integrated in the EURADOS Annual Meeting (workshops, winter schools, the intercomparison participants' sessions and the learning network, among others). Moreover, EURADOS has recently established a Young Scientist Grant and a Young Scientist Award. The Grant supports young scientists by encouraging them to perform research projects at other laboratories of the EURADOS network. The Award is given in recognition of excellent work developed within the WGs' work programme. Additionally, EURADOS supports the dissemination of knowledge in radiation dosimetry by promoting and endorsing conferences such as the individual monitoring (IM) series, the neutron and ion dosimetry symposia (NEUDOS) and contributions to E&T sessions at specific events.